Adoption and Validation of the Adolescent Stress Questionnaire for Indian High School Students - Ovine Loyster D'souza; Sucharitha Suresh; Manjeshwar Shrinath Baliga (Indian Journal of Medical Specialities)
Introduction: Adolescent stress questionnaire (ASQ) – a 58-item inventory covering broad range of adolescent distress was developed and validated for Australian adolescents. The present study reports a modification of the ASQ for the Indian context. Methodology: Initially, a focus groups study was carried out with 8 adolescents and 8 experts to understand the relevance of the subject and domain contents of ASQ using the original ASQ. Later content validation was done by the experts in the field for the modified ASQ. The modified version was administered to (n = 20) adolescents for pilot testing. In the next stage, the scale was given to 153 adolescents and readministered to the same samples after 1 week. Statistical analysis was done to ascertain the internal consistency, component factor, and test–retest reliability as per the standard analysis. Results: During stage one, 38 questions were retained which were more relevant to Indian context. The internal consistency of 6 subscales was ≥8 and measuring 0.89 for overall questionnaire. The test–retest reliability measured 0.96 for the overall scale (P < 0.0001) for each domain. During the confirmatory factor analysis, above half (20 of 38) of the items confirmed high correlations with their component scale, with factor loadings P < 0.5. Conclusion: The modified ASQ had acceptable internal consistency and test–retest reliability. Further testing with adolescent students living in other parts is recommended to provide a more complete assessment of the questionnaire.